Filial Piety Observance & Caregiving to Grandparents: The Singapore Case - Lek, Adelin Wan Ling (2017)
The research seeks to study the influence of filial piety on intergenerational grandchild-grandparent caregiving relationship in Singapore. The study uses a sociological framework combining Bengtson and Oyama’s Theory of Intergenerational Normative Solidarity, Merton’s Symbolic Interactionist Role Theory and Connidis and McMullen’s Theory of Intergenerational Ambivalence. Filial Piety refers to the demonstration of filial obligations towards one’s parents and elders. The findings revealed that filial piety continues to guide grandchildrens’ filial observance in caregiving, where grandchildren performed the role of an auxiliary caregiver. However, the perception of filial piety is not static as it is being reinterpreted by grandchildren through their everyday experiences. In face of tension between their role as a caregiver with the structural constraints and opportunities of living in Singapore, grandchildren engage in negotiation as a strategy.